A new paraprobiotic-based treatment for control of Haemonchus contortus in sheep. (December 2020) - Sanders, John; Xie, Yue; Gazzola, David; Li, Hanchen; Abraham, Ambily; Flanagan, Kelly; Rus, Florentina; Miller, Melanie; Hu, Yan; Guynn, Sierra; Draper, Austin; Vakalapudi, Sridhar; et al.
Abstract: Haemonchus contortus is a critical parasite of goats and sheep. Infection by this blood-feeding gastrointestinal nematode (GIN) parasite has significant health consequences, especially in lambs and kids. The parasite has developed resistance to virtually all known classes of small molecule anthelmintics used to treat it, giving rise in some areas to multidrug resistant parasites that are very difficult to control. Thus, new anthelmintics are urgently needed. Bacillus thuringiensis (Bt) crystal protein 5B (Cry5B), a naturally occurring protein made by a bacterium widely and safely used around the world as a bioinsecticide, represents a new non-small molecule modality for treating GINs. Cry5B has demonstrated anthelmintic activities against parasites of monogastric animals, including some related to those that infect humans, but has not yet been studied in a ruminant. Here we show that H. contortus adults are susceptible to Cry5B protein in vitro . Cry5B produced in its natural form as a spore-crystal lysate against H. contortus infections in goats had no significant efficacy. However, a new Active Pharmaceutical Ingredient (API) paraprobiotic form of Cry5B called IBaCC (Inactivated Bacterium with Cytosolic Crystals), in which Cry5B crystals are encapsulated in dead Bt cell wall ghosts, showed excellent efficacy in vitro against larval stages of H. contortus and relative protein stability in bovine rumen fluid. When given to sheep experimentally infected with H. contortus as three 60 mg/kg doses, Cry5B IBaCC resulted in significant reductions in fecal egg counts (90%) and parasite burdens (72%), with a very high impact on female parasites (96% reduction). These data indicate that Cry5B IBaCC is a potent new treatment tool for small ruminants in the battle against H. contortus . Graphical abstract: Image 1